Best Practices Top Five Prodi DIII Keperawatan Dengan Kelulusan Uji Kompetensi Tertinggi Dan Strategi Menghadapi Uji Kompetensi Sebagai Exit Exam - Ana Setiyorini; Subiyanto , Paulus; Wardani, Yulia (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
Background: The reform of higher health education in the form of a competency-based curriculum referring to the Indonesian National Qualifications Framework (KKNI) is able to produce graduates needed by the world. The national competency test for nurses still shows an alarming condition with an average graduation of <50%, the pass limit value is still below 50, although in the third period of 2017 the graduation rate increased sharply by 82.13% and first taker graduation 90.48%. It is hoped that this achievement will be maintained in next year, especially when the national examination is a graduation requirement (exit exam). Objectives: To identify the best practices model of strategies for achieving the highest and consistent nursing national competency test graduation in the five best Nursing Diploma III study programs (five stars) in Indonesia with a consistent first taker graduation rate in the last three years and strategies for preparing for national competency test as a graduation requirement (exit exam), in particular study program governance, input strategies, processes, learning outputs and special preparation of graduates to encounternational competency test Methods: Using quantitative methods with exploratory descriptive design. The sample is purposive and simple random sampling. Data collection by questionnaires, in-depth interviews, and documentation studies. Quantitative statistical analysis with frequency and percentage distributions. Qualitative analysis with data collection and data reduction, making transcripts, categorization and analysis with N-Vivo. Results and Conclusions: Input, process and output strategies affect student outcomes in the test. The character of the learning process implemented in a good SPMI framework is an important determinant of passing the test. Preparation toward the national competency test, the ability of the institution to manage students' intrinsic factors both academic and non-academic abilities as well as strategic and tactical management of extrinsic factors are needed to achieve the success of the national competenct test.